Pulsed-N2 assisted growth of 5-20 nm thick β-W films - Avyaya J. Narasimham; Avery Green; Richard J. Matyi; Prasanna Khare; Tuan Vo; Alain Diebold; Vincent P. LaBella (AIP Advances, 2015)
A technique to deposit 5-20 nm thick β-phase W using a 2-second periodic pulse of 1 sccm-N2 gas on Si(001) and SiN(5 nm)/Si(001) substrates is reported. Resistivity, X-ray photoelectron spectroscopy and X-ray reflectivity were utilized to determine phase, bonding and thickness, respectively. X-ray diffraction patterns were utilized to determine the crystal structure, lattice constant and crystal size using the LeBail method. The flow rate of Nitrogen gas (continuous vs. pulsing) had significant impact upon the crystallinity and formation of β-phase W.